STRATEGI GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MENGEMBANGKAN AKHLAK MULIA - S, Hafiq; Oktarina, Yulia; Hasanah, Dewi (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is motivated by several issues concerning the cultivation of noble character among students. The purpose of this study is to analyze the strategies employed by Islamic Religious Education and Character Education teachers in developing noble character. This study is a qualitative research using a descriptive method. The research was conducted at SMPN 14 Batang Hari. The subjects of this study include the principal, homeroom teachers, Islamic Religious Education (PAI) and Character Education teachers, as well as students of SMPN 14 Batang Hari. The research instruments used were interviews, observations, and documentation. The data analysis technique applied in this research is qualitative data analysis, which includes data reduction, data display, and conclusion drawing. The results of the study are as follows: (1) the forms of negative character traits (akhlaq mazmumah) found among students at SMPN 14 Batang Hari include mocking others, lying, breaking promises (treachery/ghadar), and egotism; (2) the strategies used by PAI and Character Education teachers to address these negative traits are role modeling, habituation, giving advice, and applying punishments; (3) the supporting factors for teachers in overcoming negative character traits include support from the school, good communication skills, and the availability of relevant teaching materials to instill character values. Meanwhile, the inhibiting factors include limited instructional time, lack of parental support, peer influence outside of school, and the suboptimal condition of facilities and infrastructure for fostering student character development.